An approach to counterculture in Mexico through the psychedelic experience and beatnik literature: an assay from anthropology - Galán López, Felipe Javier (2023)
This article presents an anthropological analysis on the psychedelic experience which I define through the influence of beatnik literature as a central cultural element, to be able to obtain a concept of counterculture that allows for its discussion, to analyze its continuity and to gain a better understanding of it. Starting from a recount of writers that have worked on the subject of counterculture and from the revision of cultural concepts, this work arises from the idea that the insurgent youth, rebelled against the mercantile conception and the technocracy of the culture through the 1960s, their way of pursuing it being through literature, hence the influence of texts and poetry by Jack Kerouac and Allen Ginsberg, provided a cultural basis to mexican counterculture, defined by Enrique Marroquín as Xipiteca.